Effect of the preparation methods on architecture, crystallinity, hydrolytic degradation, bioactivity, and biocompatibility of PCL/bioglass composite scaffolds. Issue 8 (23rd December 2014) - Dziadek, Michal; Pawlik, Justyna; Menaszek, Elzbieta; Stodolak‐Zych, Ewa; Cholewa‐Kowalska, Katarzyna
Abstract In this study, two different composition gel derived silica‐rich (S2) or calcium‐rich (A2) bioactive glasses (SBG) from a basic CaOP2O5SiO2 system were incorporated into poly(ε‐caprolactone) (PCL) matrix to obtain novel bioactive composite scaffolds for bone tissue engineering applications. The composites were fabricated in the form of highly porous 3D scaffolds using following preparation methods: solvent casting particulate leaching (SCPL), solid–liquid phase separation, phase inversion (PI). Scaffolds containing 21% vol. of each bioactive glass were characterized for architecture, crystallinity, hydrolytic degradation, surface bioactivity, and cellular response. Results indicated that the use of different preparation methods leads to obtain highly porous (60–90%) materials with differentiated morphology: pore shape, size, and distributions. Thermal analysis (DSC) showed that the preparation method of materials and addition of bioactive glass particles into polymer matrix induced the changes of PCL crystallinity. Composites obtained by SCPL and PI method containing A2 SBG rapidly formed a hydroxyapatite calcium phosphate surface layer after incubation in SBF. Bioactive glasses used as filler in composite scaffolds could neutralize the released acidic by‐products of the polymer degradation. Preliminary in vitro biological studies of the composites in contact with osteoblastic cells showed good biocompatibility of the obtained materials. Addition of bioactive glass into the PCL matrix promotes mineralization estimated on the basis of the ALP activity. These results suggest that through a process of selection appropriate methods of preparation and bioglass composition it is possible to design and obtain porous materials with suitable properties for regeneration of bone tissue. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 1580–1593, 2015.